واقع نظام التعليم عن بعد بالمركز الجامعي مرسلي عبد الله –تيبازة – -دراسة عينة من طلبة السنة أولى ميدان علوم اقتصادية وتجارية وعلوم التسيير- - شخار, نعيمة; تونسي, نجات (جامعة الوادي - University of Eloued, 2023)
لقد تم تسليط الضوء في هذه الدراسة على نظام التعليم عن بعد كونه أصبح يعد بديل لا يستهان به خصوصا في ظل الأزمات على غرار أزمة الإغلاق التي شهدتها البلاد، لقد سعى المركز الجامعي مرسلي عبد الله بتيبازة كغيره من جامعات الوطن على تبني هذا النمط التعليمي الحديث، ولقد حاولنا من خلال هذه الدراسة إبراز مدى جاهزية المركز الجامعي لتبني هذا النظام كما سلطنا الضوء على واقعه، مستعينين في ذلك بإستبانة تم من خلالها إستهداف عينة من طلبة السنة أولى ميدان العلوم الاقتصادية وتجارية وعلوم التسيير. تم التوصل من خلال هذه الدراسة إلى أن المركز الجامعي عمل جاهدا من أجل تطبيق نظام تعليم عن بعد ذو كفاءة لكن اصطدم ببعض المشاكل التي حالت دون تحقيق الأهداف المرجوة. In this study, the distance education system has been highlighted as it has become a significant alternative, especially in light of crises such as the closure crisis witnessed in the country, the University Center Marsali Abdullah Tipaza, like other universities in the country, has sought to adopt this modern educational style, and we have tried through this study to highlight the readiness of the university center to adopt this system as we highlighted its reality, using a questionnaire through which a sample was targeted. Students of the year include economic, commercial and management sciences. It was concluded through this study that the University Center worked hard to implement an efficient distance education system, by providing the appropriate climate but colliding with some lapses that prevented the achievement of the desired goals
The reality of the distance education system at the University Center Mursali Abdullah – Tipaza – -Studying a sample of first-year students in the field of economic, commercial and management sciences
مقال
Keywords: نظام التعليم عن بعد.; distance education system. Technological development, interactive dialogue process, university education, training and education.